A Case of Lung Cancer: Postop Minimal Residual Disease at Pleura - JoungSoon Jang (Hanggong uju uihakoeji, 2021)
For nonsmall cell lung cancer (NSCLC), surgery is indicated only for stage 3 as a curative measure. Even so, there is a high risk of recurrence following stage 3 lung cancer surgery, a third (33.9%) of patients experienced a cancer recurrence mostly within 2 years after surgery. The median survival time for all stages reaches only 21.9 months. For people undergoing surgery for stage 3A NSCLC, a pre-operative course of (neoadjuvant chemotherapy) can improve survival times, by improving the resectability and lowering the risk of recurrence. Pleural metastases are frequently associated with tumors of the lung and breast. Chest radiographs and computed tomography scans of pleural metastases can present as an effusion or smooth or nodular pleural thickening. In the absence of irregular or nodular pleural thickening, it is difficult to distinguish a benign from a malignant pleural effusion. To treat lung cancer, tyrosine kinase inhibitors (TKIs) recently have been used to cope with genetic mutations, apart from cytotoxic anticancer drugs. Compared to cytotoxic drugs, they are effective, have fewer side effects, and are easy to administer. Airman must have no cancer disease to apply for Class-I medical certification. Specifically, if previously operated on cancer, the cancer should not remain in the body at present, and the disease free state should persist at least one year after all kinds of anti-cancer treatments including adjuvant chemotherapy are completed. Here, this case deals with a 41-year-old pilot who has ATP license who had stage 3A NSCLC. The pilot underwent curative lung cancer surgery (lobectomy) a year ago and showed suspicious pleural metastasis at the time of his application for certification and was still using an unauthorized TKI agent alectinib (Alecensa; Roche, Basel, Switzerland).